Prevalence of Hepatitis B and Hepatitis C Virus Infection in Patients with Advanced Renal Failure: A Tertiary Care Centre Study from North Indian Population - Rungta, Sumit; Kumar, Shweta; Tripathy, Sukanya; Pandey, Sant; Verma, Kamlendra; Akhtar, Ghulam; Swaroop, Suchit; Deep, Amar (Indian Journal of Community Health, 2022)
Abstract: Viral hepatitis (Hepatitis B Virus (HBV) & Hepatitis C Virus (HCV)) related liver disease is a leading cause of morbidity and mortality especially in the patients with advanced renal failure who are treated with dialysis, and this is due to high number of blood transfusion sessions and/or cross contamination from the dialysis circuits. Aims & Objectives: This study aimed to determine the prevalence of HBV and HCV infections in patients with advanced renal failure (ARF). Materials & Methods: A cross-sectional study was done in joint collaboration of Department of Nephrology and Department of Gastroenterology, KGMU, Lucknow, from June 2018 to June 2020 among, CRF patients. Clinical data such as age, gender, duration of dialysis; number of transfusions, Serum sample was collected from each patient. Serological markers for HBV and HCV were determined with ELISA by using commercial diagnostic kits. HCV-RNA and HBV-DNA were determined quantitatively by polymerase chain reaction (PCR) assay. Results: A total 934 patients with advanced renal failure attended the nephrology OPD. Out of 934 patients, 65 (6.96%) patients screened positive for HBV/HCV infection. The results of this study also showed that the prevalence of viral hepatitis infection in the haemodialysis (HD) and without HD patients is 8.25% and 6.3% respectively. Conclusion: It has been found that viral infections, particularly HBV and HCV infections are common in advanced renal failure patients who are on HD.